Carex huangshanica (sect. Rhomboidales, Cyperaceae), a new species from Anhui, eastern China - Chen, Wei-Jie; Jin, Xiao-Feng (Phytotaxa, 2015)
Carex huangshanica X. F. Jin & W. J. Chen, a new species from Anhui Province of eastern China, is described and illustrated. It belongs to Carex sect. Rhomboidales and resembles C. longirostrata in having perigynia gradually contracted into a long beak at apex; orifice 2-lobed with long teeth; achenes abruptly contracted into a beak at apex. It differs from C. longirostrata in having upper spikes aggregated, pistillate scales shortly awned at apex, perigynia nearly glabrous, and achenes ovoid. Micromorphological characters of the perigynia and achenes under scanning electron microscope are compared between the new species and C. longirostrata. Carex huangshanica has glabrous perigynia (vs. pubescent perigynia in C. longirostrata), achenes abruptly contracted in a short curved beak at apex, and only one silica body is present in each epidermal cell (vs. achenes of C. longirostrat that are contracted in a short coiled beak at apex, and without silica body in epidermal cells).